Age-related mandibular condyle morphological variations: a panoramic radiography study at RSGMP Universitas Airlangga - Mulyani, Sri Wigati Mardi; Astuti, Eha Renwi; Wahyuni, Otty Ratna; Savitri, Yunita; Nurrachman, Aga Satria; Ramadhani, Nastiti Faradilla; Putri, Kharisma Gaprila; Jihan, Jihan (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
Objectives: This research aims to find out the variations of the mandibular condyle shape based on age on panoramic radiography. Materials and Methods: This study uses secondary data from 200 digital panoramic radiographs of patients at the dental hospital (RSGM) of Universitas Airlangga aged 20-65 years in 2019, 2020, and 2021, which have met the inclusion and exclusion criteria. Data is presented in the form of tables and graphs with simple statistical calculations, and reliability tests were carried out with intraclass correlation (ICC) methods using SPSS. Results: There are variations of the condyle shape in five age groups, the age I (20-25 Years), age II (26-35 years), age III (36-45 years), age IV (46-55 years), age V (56-65 years). Conclusion: There are condyle shape variabilities in several age groups. In age I (20-25 years), age II (26-35 years), age III (36-45 years), and age IV (46-55 years) the most variation of the condyle shape is rounded, at age V (56-65 years) the most variation of the condyle shape is rounded and pointed. Furthermore, the morphology of the condylar structures may exhibit variances and are not consistently uniform.